2020
DOI: 10.1063/1.5133049
|View full text |Cite
|
Sign up to set email alerts
|

Precision measurement of tribocharging in acoustically levitated sub-millimeter grains

Abstract: Contact electrification of dielectric grains forms the basis for a myriad of physical phenomena. However, even the basic aspects of collisional charging between grains are still unclear. Here we develop a new experimental method, based on acoustic levitation, which allows us to controllably and repeatedly collide two sub-millimeter grains and measure the evolution of their electric charges. This is therefore the first tribocharging experiment to provide complete electric isolation for the grain-grain system fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…(from Jungmann et al (2021) charging as motivation to estimate the effect for disks. The experiments by are similar in some sense to Kline et al (2020). We also study the charge on two grains before and after a collision.…”
Section: Two Particle Collision Experimentsmentioning
confidence: 81%
See 1 more Smart Citation
“…(from Jungmann et al (2021) charging as motivation to estimate the effect for disks. The experiments by are similar in some sense to Kline et al (2020). We also study the charge on two grains before and after a collision.…”
Section: Two Particle Collision Experimentsmentioning
confidence: 81%
“…This might be due to the fact that only little data exist on this. Kline et al (2020) were recently the first to publish results on high precision charge measurements in a collision experiment with charge being determined for two particles prior to and after a bouncing collision. The grains were stored in an acoustic trap before their collision and afterwards.…”
Section: Collateral Charging Of Gasmentioning
confidence: 99%
“…[7] It was reported that acoustic levitation technology can levitate liquid droplets, and further widely utilized to study areas include manipulation of subject, [8] chemical reaction, [9] material anal ysis, [10] etc. Except for liquid-liquid case, some studies using acoustic levitation to study CE between solids and solids, [11] solids and liquids [12] have been reported. We realized that the liquid droplet can be suspended in air to avoid contacting with solids and introducing extra charges [13] in the CE experiments.…”
Section: Doi: 101002/adma202102886mentioning
confidence: 99%
“…One method that allows particles to be trapped regardless of their charge is acoustic levitation. Kline et al (2020) analyzed the oscillations caused by net charge in an electric field for an acoustically trapped particle. Here, even large changes in net charge, e.g.…”
mentioning
confidence: 99%
“…However, we are rather interested in the rotational motion. So while Kline et al (2020) study the linear oscillations of grains due to their net charge in the electric field of a capacitor, we study rotational motion, as the electric field induces oscillations with characteristic frequencies trying to align electric dipoles.…”
mentioning
confidence: 99%